MANAJEMEN KEPEMIMPINAN ADAPTIF DALAM MENGELOLA PERUBAHAN KEBIJAKAN PENDIDIKAN DI SDN TARINGGULLANDEUH - Gumelar, Dede Ipan; Mustopa, Epi Saepul; Haryati, Elis; Cahyono, Rendra Bagus; Warta, Waska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the adaptive leadership management of the principal in managing educational policy changes at SDN Taringgullandeuh. Using a qualitative approach with a case study method, the research involved the principal, teachers, and staff as informants. Data were collected through in-depth interviews, participatory observation, and document analysis, and then analyzed interactively. The findings show that the principal has applied adaptive leadership principles in planning, organizing, implementing, and supervising educational policy changes, such as the implementation of the Merdeka Curriculum and learning digitalization. The principal demonstrated the ability to read the situation, collaborate with stakeholders, and maintain core school values while innovating. However, the implementation still faces obstacles, including limited infrastructure, low digital literacy among teachers, and a lack of systematic documentation and evaluation. Adaptive leadership at SDN Taringgullandeuh has proven relevant in creating a collaborative work climate and maintaining learning quality amid challenges, but it requires systemic support to be more optimal. Keywords: adaptive leadership, educational policy, school principal, policy change management, SDN Taringgullandeuh;